Comparison of Transverse Cancellous Lag Screw and Ordinary Cannulated Screw Fixations in Treatment of Vertical Femoral Neck Fractures. Issue 4 (23rd July 2019) - Dong, Qiang; Han, Zhe; Zhang, Yin‐Guang; Sun, Xiang; Ma, Xin‐Long
Abstract : Objective: To compare the clinical therapeutic effect of transverse cancellous lag screw (TCLS) fixations and ordinary cannulated screw (OCS) fixations for vertical femoral neck fractures. Methods: A total of 62 eligible patients with an average age of 56.2 years (range, 19–45 years; 40 male and 22 female) with Pauwels' type III femoral neck fractures were recruited in our study from January 2016 to December 2017. Among the patients, 30 underwent TCLS fixation (TCLS group), and the others were treated with OCS fixation (OCS group). The baseline data, perioperative outcomes (operative time, intra‐operative blood loss, reduction quality, and hospital time), postoperative outcomes evaluated by a variety of scales including visual analogue scale (VAS) score, EuroQol five dimensions questionnaire (EQ‐5D) and Harris hip scores (HHS), and complications (nonunion, femoral head necrosis, femoral neck shortening, and failure of fixation) of the two groups were recorded to compare at 12‐month follow‐up. Results: The mean follow‐up time of included patients was 13.4 ± 1.6 months in the TCLS group and 13.7 ± 0.9 months in the OCS group. There was no statistically significant difference in the baseline data as well as perioperative outcomes, including operative time, intra‐operative blood loss, the hemoglobin difference before and after treatment, quality of reduction, and hospital time between two groups. Likewise, the VAS score, the EQ‐5D score, and complications rates including nonunion and femoral head necrosis had no distinct difference in two groups. However, HHS in the TCLS group were superior to those in the OCS group at 12‐month follow‐up, and the femoral neck shortening rate was prominently reduced in the TCLS group when compared with the OCS group. Conclusions: Treating vertical femoral neck fractures with the TCLS technique could significantly improve hip functional recovery and reduce the postoperative femoral neck shortening rate. The present study provides novel insight for the treatment of vertical femoral neck fractures.